MANAGEMENT OF TOURIST VILLAGE MANAGEMENT IN BALI: STRATEGIES, CHALLENGES, AND OPPORTUNITIES - Dadang Hermawan; I Made Darsana (RADJA PUBLIKA, 2024)
This study aims to analyze the social impacts, income inequality, sustainability of community-based waste management programs, and the effectiveness of the implementation of Governor Regulation No. 10 of 2022 in managing tourist villages in Bali. A qualitative approach was employed by integrating literature studies, in-depth interviews, and policy analysis. The findings reveal that the management of tourist villages has significant social impacts on local communities, including increased economic dependence on tourism and shifts in traditional cultural values. Income inequality among tourist villages is influenced by accessibility, management quality, and infrastructure. The sustainability of community-based waste management programs relies heavily on the active participation of younger generations in fostering environmental awareness. Meanwhile, the implementation of Governor Regulation No. 10 of 2022 faces challenges such as limited accessibility to remote villages and insufficient human resource capacity. This study also highlights that digitalization, through the utilization of social media and augmented reality (AR) technology, can serve as an effective strategy to enhance the competitiveness and sustainability of tourist villages.